Self-entrepreneurship in uncertain futures: The case of performing artists in Italy - Naclerio, Emanuela (International Sociology)
Self-entrepreneurship in uncertain futures: The case of performing artists in Italy This article contributes to contemporary debates on self-entrepreneurship in cultural work by focusing on project-based theatre actors in Italy. Drawing on in-depth interviews, the study considers performing artists$1 (Bnarratives of success, unsuccess, and future expectations to shed light on how entrepreneurial projects are negotiated in neoliberal cultural work. The article expands current research by considering how self-entrepreneurial projects are lived out in insecure working environments, taking into account a geographical area and a creative sector often overlooked by studies of creative labour. In a context where precariousness is normalised, actors$1 (Bdiscourses point at the emergence of disaffection towards neoliberal entrepreneurial ideals of autonomy and competition and to the loss of a progressive idea of biographical projects. The research highlights that an ongoing status of insecurity can mine optimistic and entrepreneurial orientations, questioning the sustainability of neoliberal ethos of work as a future-oriented project in times of enhanced insecurity.- Reproduced s
Keywords: Cultural work, Insecurity, Precarious labour, Temporality, Creative work, Entrepreneurship